“It’s impossible that there’s no connection”: Autobiographical Reasoning in the Language-Learning Histories of EFL Student Teachers - Baum, Miri Tashma (Narrative Works, 2021)
Despite the growing interest in language learning histories, autobiographical reasoning, a central concept in narrative psychology, has rarely appeared in second language acquisition research, despite the fact that autobiographical reasoning has been found to be central to identity formation, correlating with resilience, motivation, and well-being. This article conducts a narrative analysis of the language learning histories of two English as a foreign language (EFL) student teachers, focusing on three qualities of their autobiographical reasoning: integration, valence, and vividness. It shows how differences in their autobiographical reasoning correlate with differences in their motivation and confidence. It also argues that production of language learning histories can contribute to the development of more confident and motivated learners and teachers.